Contractual limit of medical benefits financed from public funds. Patient’s unjust enrichment - Glanowski, Grzegorz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper describes the behavior of a patient who in order to obtain medical benefits simulates symptoms which, according to special medical knowledge could be recognised as a threat to life or health. The main problem arises when despite the fact that the limits of medical benefits financed from the public funds have run short, a medical doctor, wishing to fulfil his statutory duty, decides to render medical assistance to such patient. Whether that assistance was really indispensible can only be determined after the patient has been thoroughly examined. It may then be too late, though, and the doctor may face serious difficulty in being reimbursed by the National Health Fund, or, if there was no actual threat to patient’s life or health, such compensation for rendered service becomes out of reach. The author analyses the abovementioned situation from the civil law point of view.